Orbital blowout fracture from nose blowing. (28th June 2018) - Myers, Sam; Bell, Daniel
Abstract : Orbital blowout fractures are nearly always caused by acute trauma. Non-traumatic cases of orbital blowout fractures have only been rarely described. In this case study, we discuss an orbital blowout fracture directly caused by nose blowing. The patient developed unilateral eye swelling and orbital emphysema. It is important for the clinician to investigate all suspected orbital blowout fractures with imaging and full ophthalmological examination regardless of a trauma history. Most cases of orbital emphysema resolve spontaneously, however one must always exclude compression of the central retinal artery. This may present as acute loss of vision and/or ophthalmoplegia.